HAEMATOZOA of Some FALCONIFORMES (AVES) of Iraq - Jasim, Mohammad (Iraqi Journal of Science, 2025)
Twenty-two out of 97 specimens of falconiform birds collected at different areas of Iraq, which belong to nine species, were found infected with blood parasites. Five species of haematozoa were recovered. Microfilariae were the most common parasite with an infection rate of 12.4% followed by Haemoproteas tinnunculus, Leucocytozoon toddi, Plasmodium fallax, P. relictum and Trypanosoma avium complex with infection rates of 10.3%, 5.2%, 4.1% and 1% respectively. Two species, Leucocytozoon toddi and Plasmodium fallax are found to be new host records.